Analisis Hubungan Pesan Dakwah Radio Rodja Program Acara Kajian Untaian Mutiara Nasehat (Riyadhus Shalihin) oleh Syaikh Prof. Dr. Abdur Rozzak Al Badr dengan Tingkat Wawasan Keislaman Pendengar Radio Rodja - Luqman Luqman; Yuni Astarini (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
The purpose of this study was to determine whether effective communication between communicator with communicant and whether there is a relationship between radio propaganda messages with a level of insight Islamic rodja respondents. This research uses descriptive quantitative analytic with cross sectional approach. The object of research is Ma'had Takhossus Al Barkah Cullinan. The samples were taken by using purposive sampling with the number of respondents 65 people. The variables used were Rodja Radio Propagation Message (Effective Communicators) as the independent variable (X), Islamic Insights Respondents rate as the dependent variable (Y), and Level Respondents Hearing Event pearl strands advice as an independent variable (X1). In the test instrument using the formula Pearson Product Moment Correlation to test the validity of the program Microsoft Excel and Spearman Brown for reliability test by using Microsoft Excel. In studies with Somers'd test used to look at the relationship between the two variables. Bivariate research results are Rodja Radio Propagation message or Communicator is very effective for the respondents, existence of a relationship between Radio Propagation Message Rodja Events Pearls Strands advice by Prof Dr Shaikh Abdur Rozzak Al Badr Against Islamic Insights respondents rate and the relationship between the rate of Respondents Heard Untaian Events Pearls counsel with the level of insight into Islamic respondents.